2020
DOI: 10.21203/rs.3.rs-113486/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA SNHG17 Promotes Tumor Progression and Predicts Poor Survival in Human Renal Cell Carcinoma via Sponging miR-328-3p

Abstract: Background: Accumulating data shows that dysregulation of long non-coding RNAs (lncRNAs) are involved in human tumors' occurrence and progression. Small nucleolar RNA host genes (SNHGs) are recently revealed to play a carcinogenic role in various human neoplasms. However, the functions and underlying mechanisms of lncRNA SNHG17 in renal cell carcinoma (RCC) are still elusive.Methods: We analyzed the relationship between SNHG17 expression levels and clinicopathologic characteristics and prognosis in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Additionally, we observed that the expression of SNHG17, UBE2M, and OTUB1 was significantly correlated with a decreased infiltrating level of immune cells, indicating the immunological role of SNHG17 and its ceRNA regulatory network in prostate cancer. It has been widely recognized that SNGH17 functions as an oncogene in many cancers, such as non-small-cell lung cancer (NSCLC) [32], breast cancer (BC) [33], gastric cancer (GC) [23], and renal cell carcinoma (RCC) [34]. The tumorigenesis function and related mechanisms of SNHG17 in driving prostate cancer have also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that the expression of SNHG17, UBE2M, and OTUB1 was significantly correlated with a decreased infiltrating level of immune cells, indicating the immunological role of SNHG17 and its ceRNA regulatory network in prostate cancer. It has been widely recognized that SNGH17 functions as an oncogene in many cancers, such as non-small-cell lung cancer (NSCLC) [32], breast cancer (BC) [33], gastric cancer (GC) [23], and renal cell carcinoma (RCC) [34]. The tumorigenesis function and related mechanisms of SNHG17 in driving prostate cancer have also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have also shown that SNHG17 plays an important pathogenic role in a variety of tumor-associated diseases. Such as SNHG17 can upregulated PAX6 to exert its carcinogenic role acted as a ceRNA of miR-375 [30], promoting epithelial-mesenchymal transition (EMT) progress, proliferation and invasion of ESCC cells by sponging miR-338-3p, thereby activating SOX4 [31], and may regulate H2AX signaling via miR-328-3p in renal cell carcinoma [32]. In summary, numerous evidences indicate that SNHG17 plays an important role in tumor development and has important clinical application value in tumor diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%